Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4293/108680813x13693422521313
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Applied Laparoscopic Urology Course Using Validated Checklist

Abstract: The applied short-term laparoscopic course is an effective format particularly for laparoscopic skills in which suturing and knot tying are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…As a final step, the trained surgeon must perform surgery independently. Laparoscopic training program models in Turkey consist of visual training equipment, theoretical training starting with printed materials, animal laboratory, a fellowship program, assisting a surgeon experienced in laparoscopy, and finally performing surgery alone, under close supervision [7,8]. The period of time required for the surgeon to make and develop these techniques is known as "the learning curve."…”
Section: Resultsmentioning
confidence: 99%
“…As a final step, the trained surgeon must perform surgery independently. Laparoscopic training program models in Turkey consist of visual training equipment, theoretical training starting with printed materials, animal laboratory, a fellowship program, assisting a surgeon experienced in laparoscopy, and finally performing surgery alone, under close supervision [7,8]. The period of time required for the surgeon to make and develop these techniques is known as "the learning curve."…”
Section: Resultsmentioning
confidence: 99%
“…13 Checklists have also been shown to improve skills in the surgical training environment. These include checklists for laparoscopic training in the dry/wet laboratory environment 14 and transurethral resection of bladder tumours. 15…”
Section: Discussionmentioning
confidence: 99%
“… 7 Tunc et al reported significant improvement of laparoscopic suturing task during a 3-day dry and wet course. 8 Klein et al extrapolated that a step-wise laboratory course in vesico-urethral anastomosis (VUA) can bring an unexperienced trainee to performance skills comparable to those of a surgeon with the experience of 50 laparoscopic VUAs. 9 Several courses and training sessions are available in laparoscopy.…”
Section: Discussionmentioning
confidence: 99%